The Role of Family Communication in Shaping the Personal Resilience of Qur'an-Memorizing Students in the Digital Era - Chatia Hastasari; Siti Machmiyah; Novianto Yudha Laksana; Pratiwi Wahyu Widiarti (Universitas Negeri Yogyakarta, 2025)
This study aims to explore the role of family communication in shaping the personal resilience of Qur'an-memorizing students (santri) at Pondok Pesantren Al-Amin, Pabuaran, Purwokerto in the digital era. The process of memorizing the Qur’an is inherently demanding, especially when santri simultaneously take on the role of university students. Balancing this dual role presents complex challenges in academic, spiritual, and emotional domains. Memorizing the Qur’an requires high consistency, perseverance, and psychological stability, while university life demands effective time management and deep intellectual engagement. This dynamic often leads to imbalances, particularly in time management, stress regulation, mental and spiritual well-being, and limited direct interaction with family. Hence, santri need a support system, with the family playing a crucial role. Using a descriptive qualitative approach, data were collected through in-depth interviews with santri at the Al-Amin Islamic boarding school. The results indicate that supportive, empathetic, and continuous family communication—especially through digital platforms such as WhatsApp and video calls—significantly contributes to the development of resilience factors as defined by Reivich and Shatte: emotional regulation, impulse control, optimism, causal analysis, empathy, self-efficacy, and reaching out. Within the framework of family systems theory, two-way, stable, and open communication serves as a vital foundation for maintaining santri’s mental and spiritual health. Furthermore, advancements in digital communication technology act as emotional connectors, strengthening family bonds, yet require mindful management to preserve the quality of face-to-face interactions. This research emphasizes the importance of collaboration between families and pesantren in creating a support system that fosters the personal resilience of santri amid modern challenges.